Challenges and opportunities using hunters to monitor chronic wasting disease among wild reindeer in the digital era. Issue 1 (17th January 2023) - Mysterud, Atle; Viljugrein, Hildegunn; Hopp, Petter; Andersen, Roy; Bakka, Haakon; Benestad, Sylvie L.; Madslien, Knut; Moldal, Torfinn; Rauset, Geir Rune; Strand, Olav; Tran, Linh; Vikøren, Turid; et al.
Abstract: Surveillance of wildlife diseases poses considerable logistical challenges compared to that of humans or livestock. Citizen science can enable broader coverage, but building an efficient disease monitoring system that relies on hunters is challenging. Chronic wasting disease (CWD) is a lethal and infectious prion disease of cervids. Improving surveillance is important with the detection of CWD in wild reindeer ( Rangifer tarandus ) in Norway. This study describes the components of an efficient CWD monitoring system utilizing recreational hunters. We report the success of data capture after 6 years of surveillance. We provide an overview of CWD occurrence among the 24 wild reindeer areas and quantify the likelihood of disease absence in areas without detection. Surveillance aimed to test hunted reindeer aged ≥1 year. With higher quotas and extended hunting seasons, proactive surveillance was implemented in at‐risk areas. There were several challenges of population demarcation and the lack of surveys required for risk‐based sampling. Several specific tools for hunters have been developed, including digital apps for rapid reporting and feedback. Laboratory capacity was expanded, and novel statistical tools were developed for the specifics of the sampled tissues. The surveillance (2016–2021) achieved a sample return rate of 61.5% from a maximum of 22, 123 harvested reindeer aged ≥1 year. Among these, 64.1% included both relevant tissues (retropharyngeal lymph nodes and brain), yielding 9412 (42.5%) complete samples of harvested reindeer. Samples originating from harvest constituted 84% of total wild reindeer samples. CWD was detected in 2 of the 24 wild reindeer management areas. The remaining populations had a probability of CWD‐freedom from 60% to 99% (mean = 77%) at a design prevalence of 0.5%. Utilizing hunters to monitor wildlife disease appears to be the most realistic option for cervid species. However, the logistical and economic constraints are substantial and pose long‐term challenges. Considerable uncertainty about disease occurrence remains even after massive surveillance, and whether management should take preventive actions remains a challenge. Abstract : Utilizing hunters to monitor wildlife disease appears to be the most realistic option for cervid species. However, the logistical and economic constraints are substantial. We describe the components of an efficient chronic wasting disease (CWD) monitoring system utilizing recreational hunters—yielding 15, 369 reindeer samples.